I had a good life, it was beautiful - Rankine, Harriet Agnes, 1943- (Murray Bridge, S. Aust. : Nyiri Publications, 2008)
The life story of Harriet Rankine a member of the Ngarrindjeri people who lives in South Australia. She tells the history of her family.
"Ngarrindjeri" -- Cover.
Keywords: Rankine, Harriet Agnes, -- 1943-; Ngarrindjeri (Australian people) -- Biography; Women, Aboriginal Australian -- South Australia -- Biography; Aboriginal Australians -- South Australia -- Raukkan; Ngarrindjeri / Narrinjeri people (S69) (SA SI54-13); History - Biographies - Indigenous - Autobiographies; Child welfare - Child / parent separation; Employment - Labour market - Women; Raukkan (S.A.) -- Biography; Raukkan / Point McLeay (SE SA SI54-13); Woomera (West SA SH53-16)